2003
DOI: 10.1002/ptr.1271
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity and antitumour properties of Hypericum mysorense and Hypericum patulum

Abstract: The methanol extracts of the aerial parts of Hypericum mysorense and Hypericum patulum were tested for in vitro cytotoxicity on HEp-2, RD and Vero cell lines and antitumour activity using DLA and HEp-2 cell lines. The cell viability and morphological changes were assessed. Of these extracts, Hypericum patulum (stem) extract showed strong cytotoxicity against all the cell lines used. The CTC50 of the Hypericum patulum (stem) extract was 1.71 microg/mL for HEp-2, 1.53 microg/mL for RD and 2.23 microg/mL for Vero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…The cells were observed at different time intervals during incubation in the presence of the extracts. Cellular viability was determined by the standard MTT and SRB assay methods (12).…”
Section: In Vitro Cytotoxic Activitymentioning
confidence: 99%
“…The cells were observed at different time intervals during incubation in the presence of the extracts. Cellular viability was determined by the standard MTT and SRB assay methods (12).…”
Section: In Vitro Cytotoxic Activitymentioning
confidence: 99%
“…Hypericum mysorense is an ornamental bush found in the Konkan and Palani hills at a height of 900-1500 m. Earlier studies in our laboratory have shown significant antiviral (Vijayan et al, 2004), cytotoxic and antitumor (Vijayan et al, 2003) properties of …”
Section: Introductionmentioning
confidence: 93%
“…The percentage cytotoxicity and IC 50 were determined by the standard MTT assay method. [19] In vitro antitumor activity evaluation against cancer cells. The in vitro antitumor activity of our peptides and their FNps were determined using trypan blue dye exclusion method.…”
Section: In Vitro Antitumor Activity Studiesmentioning
confidence: 99%